One nation under God: achieving national integration through interfaith relations on the University of Abuja campus (2022)
In Contemporary Nigeria, university campuses have become veritable centres not only for religious practices but equally for the recruitment of members by sects, cults, and denominations. Our research project was premised on the assumption that for the country to achieve sustainable integration, undergraduates in the nation's university System should be co-opted as advocates and stakeholders in the onerous task of peacebuilding and interfaith harmony. This paper reports on the initial survey carried out early in the year 2022 among university of Abuja undergraduates (Christian and Muslims) in this regard. The paper used the descriptive research method. A carefully designed questionnaire was administered among five hundred and twenty-four (524) undergraduates from the University. Having deployed the Integrated Phenomenological Approach (IPA) to research, the paper found that respondents were all desirous of a peaceful interfaith space not only on their campus but across Nigeria. They opined that the introduction of a curriculum on interfaith dialogue and the formulation of a policy on religious practices in the Nigerian University System (NUS) would be a long way in entrenching peace among adherents of various religions and ultimately in promoting national integration.